Side effects of tamoxifen and raloxifene therapy - Sobstyl, Małgorzata; Tkaczuk-Włach, Joanna; Sobstyl, Jacek; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2012)
Tamoxifen and raloxifene belong to a group of selective estrogen receptor modulators (SERMs). Their features and therapeutic effects depend on tissue and hormonal environment in which they are acting. Advantages resulting from selectivity are used in treatment and prevention of breast cancer and osteoporosis. However, side effects of these therapies should not be neglected. The most common negative symptoms of SERMs treatment are endometrial hyperplasia and cancer, hot flashes, night sweats, vaginal atrophy, dyspareunia.